Local hepatic immune response in rats during primary infection with Fasciola hepatica - Tliba O.; Sibille P.; Boulard C.; Chauvin A. (Parasite, 2000)
The distribution of lymphocyte subpopulations (TCD4+ , TCD8+, TCD43+ and Ig+ cells), macrophages and eosinophils were analysed in the inflammatory infiltrates associated with hepatic lesions and in hepatic lymph nodes (HLN) from rats experimentally infected with F. hepatica and necropsied 1, 2, 3, 4, 6 and 8 week post infection (WPI). We also investigated the fixation of immunoglobulin isotypes on migrating flukes in the liver. As early as 1WPI, portal tract areas surrounding migratory tunnels were infiltrated with immune and inflammatory cells. The dominant cells were eosinophils and to lesser extent, macrophages and lymphocytes (TCD4+, TCD8+ and B). Most of the inflammatory and immune cells reached the posterior part of flukes, whereas in front of the parasites these cells were fewer in number. Except for eosinophils, no immune cells penetrated through granuloma consisting of hepatic necrotic cells. As early as 1WPI, IgM could be detected in the liver, and to a lesser extent IgA, IgG2a and IgG2b. At 2WPI, IgE and IgG1, began being detected. IgG2c was detectable at 3WPI. In HLN, we observed numerous microscopic follicles in the cortical zone with proliferation of germinal centres and medullary cords. The protective role of infiltrating cell populations and immunoglobulin isotypes and possible mechanisms of immune evasion by the parasite are discussed.